The European Court of Human Rights and minority religions: messages generated and messages received. Issue 3 (2nd October 2017) - Fokas, Effie; Richardson, James T.
ABSTRACT: This contribution introduces a collection of studies focused on engagements of religious minorities with the European Court of Human Rights (ECtHR). Setting out first the global importance of the ECtHR as a standard setter in the protection of the rights of religious minorities, the text goes on to introduce the ten contributions that together make up the present special issue on the European Court of Human Rights and Religious Minorities. Beyond briefly summarising the contexts of the special issue, this contribution indicates that the first part of the special issue entails critical assessments of some of the Court's case law dealing with religious minority claims (exploring on their clarity and consistency – or lack thereof – and controversiality), and that the second part offers insight into the grassroots level impact of the Court's case law on religious minority claims. It explains how each of these contributions deepens our understanding of the ECtHR in its approach to and impact on religious minorities. And it introduces the fact that, rather uniquely, this collection of texts offers a rare vantage point on the 'circle of life' of the Court's case law on religious minorities.